PHYSICOCHEMICAL PROPERTIES OF NATURALLY BREWED BEVERAGE OF PLETEKAN LEAVES (Ruellia tuberosa L) WITH ADDITION OF NATURAL FLAVORS - Retno Prasetia; Muh. Doddy Pratama; Pratiwi Jati Palupi (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Pletekan leaves (Ruellia tuberosa L) is used as traditional medicine for diabetic because of the presenting of flavoloid (polyphenol). The aim of this research was to improve the taste of brewed beverage thus itincreases community appeal to consume. This study used completely randomized design (RAL) with 4 treatments (flavor varians: bay leaves, cinnamon, ginger, and pandan leaves with ratio of natural flavor to pletekan leaves 0.5:1) and three replications. The parameters analysed were chemical test (the percentage of water, total phenolic, tannin, antioxidant activity), and organolepticresults (hedonic test) that was analysed with ANOVA at 5% level. The results showed that the percentages of water in all the dried sample for making brewed beverage were in the range of 5,33% – 8%. The combination of pletekan leaves and cinnamon gave the highest total phenolic and tannin concentration (88,73 ± 0,07 mg GAE/10 g sample and 143,63 ± 0.31 mg/L) but having the second highest oxidant activity after DP+DS combination. The organoleptic results showed that the combination of brewed DP+KM had different taste as preferred taste. This combination also gave the highest preferred color but no significant different than others. Because there were no differences in oudor and texture of bewed beverage, thus the combination of DP+KM was the best combination in giving the preferred taste of beverage.